Harnessing photosynthetic and morpho-physiological traits for drought-resilient soybean: integrating field phenotyping and predictive approaches - Singh-Bakala, Harmeet; Ravelombola, Francia; Adeva, Cheryl; Oliveira, Maiara; Zhang, Ru; Argenta, Jessica; Shannon, Grover; Lin, Feng (Frontiers in Plant Physiology, 2025)
IntroductionDrought stress is a major constraint for Soybean (Glycine max (L.) Merr.) productivity, exacerbating yield instability under current and predicted environments. Breeding drought resilient soybean varieties requires more robust selection markers for improved accuracy.MethodsTo identify the traits associated with field drought tolerance, we evaluated photosynthetic and other morpho-physiological traits in elite soybean germplasm at drought sensitive reproductive stage (R2-R3). Using chlorophyll fluorescence phenotyping and mixed model analysis, we assessed genotypic variability in various photosynthetic and morpho-physiological traits under irrigated and rainfed field conditions.ResultsTolerant genotypes (higher yield stability) exhibited significantly higher SPAD, NPQt, and FvP/FmP under drought, along with reduced leaf thickness. Multivariate analyses suggested these photosynthetic and morpho-physiological traits as key indicators of yield stability under drought. By coupling with soil parameters, these traits were able to explain 74-79% of yield variance in predictive models.DiscussionThese findings suggest that SPAD, NPQt, FvP/FmP, and leaf thickness are valuable markers for identifying drought-tolerant genotypes. Integrating these traits into selection criteria could improve the accuracy of breeding programs aimed at developing drought-resilient soybean varieties. Future efforts should validate these markers across diverse environments and leverage genomic tools to accelerate allele discovery, offering a pathway to climate-resilient soybean production.